1988
DOI: 10.23986/afsci.72340
|View full text |Cite
|
Sign up to set email alerts
|

Silage intake and milk production in cows given barley or barley fibre with or without dried distillers solubles

Abstract: Abstract. Twenty Friesian cows in four pens were arranged in a 4x4 Latin Square with a 2 x 2 factorial arrangement of treatments to evaluate the effect of barley fibre with solubles and dried distillers solubles (DDS) as a protein supplement on silage intake and milk production. Each experimental period lasted 4 wk, during which the cows were given ad libitum silage with one of the four supplements: barley (B), barley + DDS (BD), barley fibre (F) and barley fibre + DDS (FD). All the supplements were given at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 10 publications
2
10
1
Order By: Relevance
“…Similar effects of distiller's solubles on calculated utilization of ME were observed in our previous studies (Ala-Seppälä et al 1988;Huhtanen et ai. 1991).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar effects of distiller's solubles on calculated utilization of ME were observed in our previous studies (Ala-Seppälä et al 1988;Huhtanen et ai. 1991).…”
Section: Discussionsupporting
confidence: 88%
“…Increasing dietary crude protein (CP) concentration by including dried distiller's solubles (DDS) in a grass silagebased diet had no effect on milk yield or milk composition (Ala-Seppälä et al 1988). In contrast, increasing protein content in the supplement by including soybean meal or fish meal has consistently increased milk yield in cows given grass silage ad libitum (Thomas and Rae 1988;Chamberlain et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…For the S treatment, no difference in silage DMI between concentrates was noticed, but for the F treatment the silage intake was lower with the more fibrous concentrate B than A. Contrary to our results, Ala-Seppä lä et al (1988), Huhtanen et al (1988) and Aston et al (1994) measured increased silage intake when starchy concentrates were replaced by more fibrous concentrates. In these earlier studies the concentrate was given twice a day, whereas in our study the concentrate was given from computerized concentrate feeders during five feeding periods.…”
contrasting
confidence: 99%
“…Diets containing fibrous byproducts supported higher ruminal pH than diets with starch-rich concentrates (Ørskov and Oltjen, 1967;Martin et al, 1994). Therefore feeding fibrous concentrates may increase the intake of grass silage, and thus energy, as shown in the study of Ala-Seppä lä et al (1988). However, to our knowledge there is no study focusing on the effect of concentrate composition with different rates of increase in concentrate allowance during the first weeks of lactation on substitution rate and cows' performance.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated energy value of barley fibre was about 90% that of barley. Results with dairy cows showed that there was either no difference in the milk yield ofcows given barley or barley fibre (Huhtanen et al 1988) or milk yield was higher with barley fibre diets (Ala-Seppälä et al. 1988).…”
mentioning
confidence: 99%